2013
DOI: 10.1088/1674-1056/22/1/013101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electron correlation on high-order harmonic generation in helium model atom

Abstract: High-order harmonic generation (HHG) of a helium model atom in an intense laser field has been numerically investigated. The influence of electron correlation on HHG is analysed by changing the strength between the electrons. The numerical results show that as the electron interaction strength becomes small, the first ionization energy increases rapidly, which results in the decrease in ionization. So the conversion efficiency of the high harmonic lying in the plateau decreases greatly, while the cutoff harmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Compared with the SAE calculations, the correlation effect of electrons in the time-dependent field can change the harmonic strength, cutoff energy, and result in a new broader structure in the higher energy region due to resonance between the intermediate state and the ground state. [28,29] Since we compare only the relative HHG spectra, our conclusion given below will remain even after considering the correlation effect.…”
Section: Hhg Of LI + In the Combined Laser Fieldmentioning
confidence: 99%
“…Compared with the SAE calculations, the correlation effect of electrons in the time-dependent field can change the harmonic strength, cutoff energy, and result in a new broader structure in the higher energy region due to resonance between the intermediate state and the ground state. [28,29] Since we compare only the relative HHG spectra, our conclusion given below will remain even after considering the correlation effect.…”
Section: Hhg Of LI + In the Combined Laser Fieldmentioning
confidence: 99%
“…[18,19] Recently, Luo et al [20] have shown dramatic cutoff extension and broadband supercontinuum generation in multi-cycle two-color pulses, which can directly generate an isolated sub-100-as pulse. Hu et al [21] proposed effect of electron correlation on high-order harmonic generation of He model atom. Li et al [22] theoreti-cally achieved an isolated 26-as pulse of He + by means of an intense few-cycle chirped laser field.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In these applications, how to effectively extract the harmonic signal from the mixed signal which is interfered by chaotic signal has very important theoretic and practical significance. [2,3] Leung et al [4] estimated the harmonic signal amplitude and frequency in chaotic interference background by the minimum phase space volume method. Haykin and Li [5] studied the small target signal extraction from sea clutter signal with chaotic characteristic by artificial neural network.…”
Section: Introductionmentioning
confidence: 99%